Cardiac workload of dressers in underground manual coal mines - Saha, R; Samanta, A; Dey, NC (Journal of Institute of Medicine Nepal, 2011)
Introduction: Occupational disorders invite absenteeism amongst the miners. Though rapid technological advancement has happened, yet assessment of cardiac workload was largely ignored in underground coal mines in India. Methods: Physiological stress was evaluated in terms of working heart rate, net cardiac cost and relative cardiac cost. Heart rate was measured during their course of work by heart rate monitor at the coal face. Recovery heart rates and environmental heat load were also assessed. Results: Heart rate was found to be 117 and 122 beats/min respectively in first and second spell. NCC (49.7 and 54.8 beats /min) and RCC (47% and 52%) exhibit significant variations between spells, whereas rate of recovery had been very poor amongst the workers who regularly exceeded recommended levels of cardiac strain indices. The nature of work depicted it as a heavy job although recovery trend categorizes it heavier than that. ET and WBGT were above the recommended limits as per the guidelines of WHO and ACGIH. Conclusions: High physiological demand of the job with towering heat stress was found to hinder the recovery process and may cause deleterious impacts on the workers. Ergonomic interventions were highly felt towards job organization and up gradation of environmental conditions. Keywords: Coalmines; dressers; workload DOI: http://dx.doi.org/10.3126/joim.v32i2.4938 Journal of Institute of Medicine, August, 2010; 32: 11-17